FAMILY CONTROL AND EARNINGS MANAGEMENT IN BRAZILIAN LISTED COMPANIES: A RELATIONSHIP MEDIATED BY AGE - Tommasetti, Roberto; Macedo, Marcelo Alvaro da Silva; Constantino, Fabricia de Farias da Silva; Sarlo Neto, Alfredo (Revista Universo Contábil, 2019)
A family-owned company potentially represents the realm of the agency theory because, if on one side this kind of organization shows lower Type I agency conflicts due to the proximity between ownership and management, on the other side it emphasizes Type II conflicts, within ownership, between majority and minority shareholders. In this situation, the literature suggests a positive and a negative impact of the family control on earnings quality, named alignment and entrenchment effect respectively. The socioemotional wealth (SEW) theory also associates the presence of the family-owner to debatable consequences, since SEW preservation attitude can affect the business decision-making process, especially in the first phase of family firm’s life where family objectives have priority over business objectives. The present study aims to investigate the influence of the family control in the quality of earnings, answering the following research questions: (i) do family firms engage less in earnings management than non-family firms? (ii) does the relation between family ownership and earnings management differ between younger and older family firms? The main finding is that old family firms engage less than any other group subsample in earning management practices, questioning literature that mainly considers family firms to be a homogeneous category.